2019
DOI: 10.32615/ps.2019.104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyamines on agronomic traits and photosynthetic physiology of wheat under high temperature stress

Abstract: Two spring wheat varieties were used to study alleviating effects of exogenous spermine (Spm) and spermidine (Spd) on agronomic traits and photosynthesis under high temperature treatment (HT). Our results showed that HT significantly decreased grain mass per panicle of heat-resistant variety (XC 6) by 25% and heat-sensitive variety (XC 31) by 32%. After HT, i.e., at 13 d after flowering, the decrease in net photosynthetic rate of XC 6 (38%) was lower than that of XC 31 (53%); the reason for this was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Both the CO 2 assimilation capacity and electron transport processes including the PS II activity showed a decline above a critical temperature value. It has also been demonstrated previously, that heat acclimation alters both the light and dark reactions of photosynthesis (Jing et al 2019). However, even if the changes contained common elements, they varied depending on genotypes.…”
Section: Discussionmentioning
confidence: 60%
“…Both the CO 2 assimilation capacity and electron transport processes including the PS II activity showed a decline above a critical temperature value. It has also been demonstrated previously, that heat acclimation alters both the light and dark reactions of photosynthesis (Jing et al 2019). However, even if the changes contained common elements, they varied depending on genotypes.…”
Section: Discussionmentioning
confidence: 60%
“…This indicates that the electron transfer of photosynthetic electrons was blocked, and the efficiency of photosynthetic pigments converting light energy into chemical energy decreased. 47 , 48 Pretreatment with exogenous Spd under HT stress could improve ΦPSII, but reduce NPQ, which might be that exogenous Spd could protect PSII from excessive energy damage, and enhance the stability of the reaction center of the photosystem, 18 which is conducive to the conversion of light energy into chemical energy, thereby providing enough energy for carbon assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…It enhances photosynthesis and HT tolerance in wheat. 18 Moreover, the Spd pretreatment alleviates the negative effects of HT on the photochemical efficiency of the photosystem II (PSII) of lettuce seedlings. 19 , 20 Furthermore, exogenous Spd regulates antioxidant enzyme activity, reducing superoxide anion rate and malondialdehyde (MDA) content to maintain plant cell membrane stability.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, clear evidence was found about a positive correlation between CH, the leaf RWC, and the Na content, which also positively correlates with the weight of 100 kernels and the total kernels weight ( Figure 6B ). It can be because the application of PAs under stress has been reported to protect the photosynthetic apparatus (ensuring the synthesis of photosynthates) and increase the osmotic adjustment of the plants under stress conditions ( Chen et al, 2019b ; Jing et al, 2019 ). Moreover, Xu et al (2016) suggested that PA might be involved in the starch biosynthesis in kernels during post-anthesis when the soil is drying.…”
Section: Discussionmentioning
confidence: 99%